Color stability of nanohybrid and microhybrid composites after immersion in common coloring beverages at different times: a laboratory study - Ahlam Mohammad Al-Shami; Mohammad Ali Alshami; Abdulwahab I. Al-Kholani; Amat-Alkhaliq Moham (Nature Publishing Group, 2023)
Abstract Objective/Aim This in vitro study aimed to evaluate the color stability of microhybrid and nanohybrid restorative composites after exposure to immersion media common in Yemen for different periods. Materials and methods Two composite materials, nanohybrid Tetric N-Ceram and microhybrid Te-Econom Plus, were investigated. Six groups of 30 cylindrical specimens (n = 5/group; diameter, 10 mm; thickness, 2 mm; shade A2) of each restorative material were immersed for 1 week in distilled water, qat solution, Yemeni coffee, traditional Yemeni coffee (qishr), red tea, and Dilsi cola. Color changes were evaluated by colorimetry. The color data and pH were measured before and 1, 3, and 7 days after immersion. The data were statistically analyzed. Results Tetric N-Ceram showed lesser discoloration than did Te-Econom Plus. Qat, coffee, and red tea caused highly significant discoloration than did Dilsi cola and distilled water (p < 0.05). The role of low pH in discoloration depended on the colorant. Discussion Nanohybrid Tetric N-Ceram composites are more resistant to discoloration than are microhybrid Te-Econom Plus composites. Qat and coffee have the highest effect on composite discoloration. Conclusions These findings will aid in selecting composite materials and patient instruction.